Tenth Grade Female Students' Acquisition of Jurisprudential Provisions Related to Women in Textbooks of Islamic Education in Oman - Maimuna Al-zedgali (Sultan Qaboos University, 2014)
The aim of this study was to identify the jurisprudence provisions related to women, included in the textbooks of the second cycle (grades 5-10) of basic education. To achieve this, a list of these provisions, consisting of 65 items and an achievement multiple-choice test were prepared. After confirming the validity and reliability of the two instruments, the test was administered to a sample of 280 tenth grade students. The most important findings of this study were: Imbalance in the distribution of provisions according to class/grade, where most of the provisions are focused the textbook of the seventh grade. The degree of students' acquisition of these provisions was 70.39% which is less than the educationally acceptable level set by the researcher at 75%. The study made a number of recommendations, including the need to achieve balance and diversity in the distribution of jurisprudence provisions relating to women in the second cycle (grades 5-10) of basic education.